The Role Of Agroforestry Towards Local Culture And Agroforestry Farmer Attitudes Towards Its Environment In Bulungan District, North Kalimantan Province: Peran Agroforestri Terhadap Budaya Lokal Dan Sikap Petani Agroforestri Terhadap Lingkungannya Di Kabupaten Bulungan Provinsi Kalimantan Utara - MARLAN USMANI PUTRA (Universitas Widya Gama Mahakam, 2020)
The Agroforestry System in Mara Satu village largely follows traditional patterns. The reason the farmers apply the agroforestry pattern has become a local culture that was passed down from their ancestors. The community of farmers is still very dependent on the commodity yields from the agroforestry system, but the community is not aware that agroforestry also affects the local culture, including the attitude of farmers to their environment. Regarding cultural aspects, agroforestry can play a role in tenure aspects, preserving various cultural identities, maintaining local institutions, and preserving traditional knowledge, while looking at farmers attitudes towards the environment, they can assess their attitudes towards grazing forested animals, harvesting forest products and attitudes of agroforestry farmers in maintaining staple plants. so this study aims to determine how the role of agroforestry in local culture and how the attitude of agroforestry farmers to their environment in the village of Mara Satu, Bulungan District. This research was conducted in the village of Mara Satu, Tanjung Palas Barat District, Bulungan Regency, North Kalimantan Province. The methodology used is a purposive sampling method that is deliberate sampling while the determination of the number of samples is determined based on the Slovin technique. Data analysis using quantitative descriptive and loaded in tabular form. Based on the results of the study it can be seen that agroforestry practices developed by farmers in the village of Mara Satu play an important role in protecting farmer's tenure rights, preserving cultural identity, enhancing the role of local institutions, and preserving traditional knowledge. Agroforestry farmers in Mara Satu village can also be said to be quite concerned about their environment. This is evidenced by the majority of agroforestry farmers not tending livestock in the forest and they no longer cut wood in the forest for sale but benefit from non-timber forest products such as swallow nests (Collocalia maxima), aloeswood (Aquilaria malaccensis), lapiu fruit (Archidendron panviflorum) and honey bee (Apis koschevnikovi) from the forest. Besides that, Mara Satu village farmers always take care of their agroforestry staple plants, in this case, durian (Durio zibethinus), as well as they, take care of other forest plants, although the intensity of each respondent varies, because they realize that it is very important to maintain the forest.